With Solvent Extraction Method, and via new Organic Reagent 2-(Benzo thiazolyl azo)-4,5- Diphenyl Imidazole for Spectrophotometric Determination of Copper (II) in different Samples - Baghdad Science Journal (مجلة بغداد للعلوم, 2014)
The new organic reagent 2-[Benzo thiazolyl azo]-4,5-diphenyl imidazole was prepared and used as complexing agent for separation and spectrophotometric determination of Cu2+ ion in some samples include plants, soil, water and human blood serum. Initially determined all factors effect on extraction method and the results show optimum pH was (pHex=9), optimum concentration was 40?g/5mLCu2+ and optimum shaking time was (15min.), as well stoichiometry study appears the complex structure was 1:1 Cu2+: BTADPI. Interferences effect of cations were studied. Synergism effect shows MIBK gave increasing in distribution ratio (D). Organic solvent effect appears there is no any linear relation between dielectric constant for organic solvent used and distribution ration (D). Thermodynamically found the reaction was Endothermic reaction, with ?Hex= 0.0131 KJ.mole-1,?Gex=-54.20 KJ.mole-1 ,?Sex= 167.84 J.mole-1.Beer’s law was obeyed over the concentration 1-30?g/5mL, and ?=922.90 Lmol-1.cm-1,with detection limit 1.7×10-5and Sandell’s sensitivity 6.8× 10-7 gcm-2.